Muck Problems in Subway Shield Tunneling in Sandy Cobble Stratum - Cui Kai; Lin Weikang (Polish Maritime Research, 2016)
Experiments aiming at the muck improvement for Chengdu’s subway shield tunneling in water-rich sandy cobble ground initially finds out the kinds and ratio of muck improver suitable for the this strata, and through the field application determines the reasonable ratio of muck improver for shield tunneling in sandy cobble ground, providing a reference to other muck improvement for shied tunneling in similar ground. And the earth pressure balanced shield is widely used in tunnel engineering, with its characteristics as wide adaptability, safe operation, fast driving speed, low environmental noise and low cost. Taking Chengdu Metro Line as the background, aiming at the difficulty faced by EPB shield tunneling in water-rich sandy cobble ground, and based on the explorations and researches of the predecessors and scholars, engineering and technical personnel, the present paper combines with engineering examples to make a systematic summary and research on key construction technology of EPB shield tunneling through sandy cobble ground from the aspects of EPB shield adaptability, , structure and transformation of cutter and helical unearthed wares, settlement control method, and muck improvement measures. It has certain reference value and guiding significance to the selection of shield machine and the reconstruction of shield machine in complex geological condition.